REAL-TIME DATA INTEGRATION FOR SEAMLESS OMNICHANNEL RETAIL - Kapil Pothakanoori, (INTERNATIONAL JOURNAL OF COMPUTER ENGINEERING AND TECHNOLOGY (IJCET), 2024)
As consumer expectations evolve, real-time data integration is essential for providing a seamless omnichannel retail experience that unifies physical stores and online platforms. This article investigates innovative strategies for integrating sales, customer data, and inventory across multiple channels, enabling retailers to deliver consistent and personalized customer experiences. By leveraging cutting-edge cloud-based architectures and edge computing, retailers can synchronize data between in-store devices and centralized cloud systems in real-time, bridging the gap between physical and digital retail environments. Key to this approach is designing real-time data flows that ensure continuous synchronization of stock levels, promotions, and customer profiles across all touchpoints, whether in-store, online, or through mobile apps. The article explores the use of event-driven architectures and microservices to manage the complexity of omnichannel data integration, allowing retailers to respond to customer actions instantly. The article also addresses the challenges of integrating legacy systems with modern cloud platforms, a common hurdle in traditional retail environments, examining techniques for modernizing these systems through APIs, middleware, and data transformation layers. Case studies from leading retail brands demonstrate how real-time data integration has been successfully implemented to create unified customer journeys, improve inventory accuracy, and enhance decision-making with real-time insights.